1998
DOI: 10.1088/0953-8984/10/36/012
|View full text |Cite
|
Sign up to set email alerts
|

Study of intrinsic point defects in oxides of the perovskite family: II. Experiment

Abstract: The electrical conductivity of and perovskite-type oxides converted by vacuum annealing into states with weak and strong compensation between donors and acceptors has been measured. It was shown that the reduced samples had both shallow and comparatively deep levels which were attributed to the neutral and singly-charged oxygen vacancy, respectively. The experimentally determined activation energies are consistent with the results of the theoretical computation reported in Part I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 24 publications
9
26
1
Order By: Relevance
“…This is consistent with previous theoretical studies 6 and with experimental estimates which indicated a very small ionization energy for the oxygen vacancy, of the order of 0.4 eV. 44 Optical measurements suggest that the presence of oxygen vacancies induce states slightly below the conduction band edge, 45 although these assignments are not unambiguous.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous theoretical studies 6 and with experimental estimates which indicated a very small ionization energy for the oxygen vacancy, of the order of 0.4 eV. 44 Optical measurements suggest that the presence of oxygen vacancies induce states slightly below the conduction band edge, 45 although these assignments are not unambiguous.…”
Section: Discussionsupporting
confidence: 89%
“…5, show that by creating the vacancy, a new occupied state appears in the gap, at 3.4 eV above the top of the valence band and 0.8 eV below the bottom of the conduction band ͑singlet state͒. This is consistent with experimental estimates which indicated an ionization energy for the neutral oxygen vacancy of the order of 0.4 eV, 44 and with optical measurements which suggest the presence vacancies-induced states slightly below the conduction band edge. 45 A second empty state is very close to the first one, Fig.…”
Section: The Neutral O Vacancy In Srtio 3 : Periodic Calculationssupporting
confidence: 81%
“…Due to existence of different kinds of bonds in SrTiO 3 one can observe a competition between the tendency to trap the electrons associated with the missing oxygen in vacancy (F center) or to localize them on the Ti 3d orbitals. The creation of a neutral O vacancy results in the new electronic state below the conduction band, which is consistent with experimental estimate indicated small ionization energy for the oxygen vacancy [30]. Defect band is mainly composed of 3d(z 2 ) energy levels of the two Ti ions directly above and below the vacancy.…”
Section: Discussionsupporting
confidence: 88%
“…Recent experimental work by Raevski et al [35] has found that the neutral oxygen vacancy is at a shallow level with an energy of several meV in BaTiO 3 and SrTiO 3 and the singly charged oxygen vacancy is a relatively deep level at 0.5-0.6 eV and 0.3-0.4 eV below the conduction band minimum (CBM) in BaTiO 3 and SrTiO 3 , respectively. Mizushima et al also found singly charged oxygen vacancies residing at a energy level of 0.2-0.3 eV in La (donor)-doped SrTiO 3 [36].…”
Section: Resultsmentioning
confidence: 99%